Russia's sorry infrastructure. - Oberg, J.
The loss of the nuclear submarine Kursk and the fire in Moscow's TV tower are indications of an infrastructure in grievous disrepair. The outlook for Russia's technological infrastructure remains grim, experts insist. Almost 70 percent of the population drinks water unfit by US standards. One-third of waste water is released untreated. Railways, electricity, oil and gas pipelines, roads and bridges all need massive infusions of cash. The Russian national electric grid will need at least 70 billion dollarsover the next five to seven years to maintain current levels of power output, or the country will face a severe energy crisis as the power distribution system collapses. The Emergency Situations Ministry issued an apocalyptic prediction that Russia was becoming vulnerable to innumerable technological disasters, such as fires, collapsing buildings, radiation leaks, pipeline ruptures, and toxic spills. Experts warned that much of Russia's industrial equipment might become virtually useless within five years. The estimated cost of these repairs is about a hundred billion dollars, about five times the total annual budget of the Federal government.
Keywords: Emergency Situations Ministry; Kursk nuclear submarine; Moscow TV tower fire; Russia; Russian national electric grid; Collapsing buildings; Industrial equipment; Pipeline ruptures; Power distribution system; Radiation leaks; Railways; Technological infrastructure; Toxic spills; Unfit drinking water; Untreated waste water